How to understand quantum chemical computations on DNA and RNA systems? A practical guide for non-specialists - Šponer, Jiří; Šponer, Judit E; Mládek, Arnošt; Banáš, Pavel; Jurečka, Petr; Otyepka, Michal (Methods (San Diego, Calif.), 2013)
In this review primarily written for non-experts we explain basic methodological aspects and interpretation of modern quantum chemical (QM) computations applied to nucleic acids. We introduce current reference QM computations on small model systems consisting of dozens of atoms. Then we comment on recent advance of fast and accurate dispersion-corrected density functional theory methods, which will allow computations of small but complete nucleic acids building blocks in the near future. The qualitative difference between QM and molecular mechanics (MM, force field) computations is discussed. We also explain relation of QM and molecular simulation computations to experiments.
Keywords: Computer Simulation; Molecular Dynamics Simulation; konformace nukleové kyseliny; Models, Molecular; DNA; Molecular mechanics; simulace molekulární dynamiky; molekulární modely; Molecular structures and energies; Quantum chemistry; DNA structure; Nucleic Acid Conformation; RNA; počítačová simulace